What we Learned from Covid19 on behalf of Hospital Management? - Malhan S; Torgay A; Kavuncubası S; Alzhanov S; Kikimbayeva R; Malchenko V; Zhunussov Y; Haberal A (Global Journal of Medical and Clinical Case Reports - Peertechz Publications, 2020)
Aim: Our aim is to take an attention to hospital management concept during COVID19. Method: We searched pubmed with key words ; hospital, management, and COVID and reached 2054 articles. 1881 articles were full texts. We searched all abstracts and determined 357 systematic review and meta-analysis. But only 40 articles were directly related to hospital management and COVID-19. 40 articles were interpreted and areas for hospital managers to study were determined.  Result: The articles about hospital management are not enough to reference to other countries. So countries should publish their experiences and also we have to learn cost of COVID in order to find good practices for hospital management Conclusion: Literature needs more articles about hospital management concept.